The epidemiology & molecular basis of fluoroquinolone resistant & susceptible isolates of Campylobacter coli - Cooper, Rhett (Division of Medical Microbiology, 2017)
Fluoroquinolone susceptible and resistant Campylobacter coli were isolated from pigs on two separate pig farms. C. coli are enteric pathogens of humans and animals and although diarrhoea resulting from C. coli and C. jejuni is generally a self-limiting disease, in severe cases, fluoroquinolones are the choice antibiotic for treatment. The presence of fluoroquinolone resistant C. coli strains in the food chain is cause for concern as this may be a source of resistant strains in humans. Sixty-one isolates were included in the study: 26 were susceptible to nalidixic acid and ciprofloxacin and 35 were resistant to these antibiotics. Fifty-five strains were obtained from pigs on farm A, while 6 strains were obtained from pigs on farm B, the source farm of pigs to farm A. Serotyping and flaA typing were carried out to study the epidemiology of the isolates. Serotyping identified 0:24 (11/61) as the most frequent serotype isolated, followed by 0:5 (7/61). Common serotypes 0:48, 0:54 and 0:59 were identified in strains from both farms. A high number of the strains were non-typeable (23/61) but were distinguished by flaA typing. RFLP analysis of the flaA gene revealed 13 distinct profiles in strains from farm A, and 4 profiles in strains from farm B, of which only 1 was unique to farm B. Profile 1 was the commonest profile observed with 31 % (17 /55) of flaA typed strains in this profile. There was an association between 0:24, profile 6, and resistance. Resistant and sensitive pairs were isolated from 15 pigs; flaA profiles of each of 4 pairs were identical, suggesting selection of resistant mutants from previously sensitive populations. An investigation of the molecular basis of the fluoroquinolone resistance identified a Thr-86 to Ile mutation in GyrA, the primary target of these antibiotics.